Preliminary Analysis of Two Medicinal Plants against causative organism of Bovine Mastitis - Gopinath S.M,; Suneetha T.B,; Mruganka,; V.D,; V.D, Ananda S, (International Journal of Phytomedicine, 2011)
Bovine Mastitis is an intramammary infection which is most common among the dairy cattle and continues to be the most costly disease to the dairy farmers. Presently, antibiotics are used for treatment of mastitis leading to the development of antibiotic resistant strains and consumer health problem. The present study investigates in vitro antibacterial activity of leaves of two medicinal plants namely Cymbopogon citratus and Punica granatum L against causative organisms of bovine mastitis. Aqueous and methanol extracts of two plants were investigated by agar well-diffusion method. Methanol and aqueous extracts of leaves of Cymbopogon citrates and Punica granatum L. were found to possess potency against infectious pathogens Staphylococcus aureus, Coagulase negative Staphylococcus aureus, Streptococcus uberis and Escherichia coli isolated locally from clinical and sub clinical samples of Mastitis from Karnataka region whereas .Phytochemical screening of the plants revealed mainly the presence of alkaloids, tannin, saponin, terpenoids and falvonoids.